EFFECT OF SPIRITUAL ALIENATION OF THE PERSON UNDER GLOBALIZATION CONDITIONS (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2023)
This article is focused on the issue of moral alienation of the individual in the context of globalization, and the issues of strategic importance of the problems of moral alienation of the individual are analyzed. Also, the article raises the priority issues of preventing the spiritual alienation of a person in the conditions of globalization, and presents various methods and means of solving it.